Mental Juara pada Atlet Bulutangkis Indonesia : Studi Theory of Critical Moments dan Self Determination dalam Psikologi Olahraga - Ardiningtiyas Pitaloka; Andin Andiyasari (Fakultas Psikologi Universitas Pancasila, 2011)
Sport is an activity that presenting sense of purpose and sense of continuous challenge. Athlete's best performance will be achieved when the athlete is totally involved, focused and absorb in the game. Carlstedt (2004) presented the theory of critical moments which emphasizes on the importance of psychological factor than any other factors. A winner-mentality athlete or toughness mental has a certain psychological pattern which is called Primary Higher Order (PHO). This pattern is a combination of low or high absorption, low neurotics (worry) and high repressive coping (RC). Athlete's best performance is also relvated with intrinsic motivation, as it is mentioned in the theory of self-determination. This research analyzed the performances of four international badminton athletes based on the theory of critical moments and self-determination. The analysis covered 82 graphs of the game of the research subjects. The result showed that there were no significant differences in the four research subjects in the term of game technical skill, but there was a difference in the pattern of psychological factor and self-determination.